OPTIMALISASI KESELAMATAN KERJA PERAWAT MELALUI PENINGKATAN KEPATUHAN TERHADAP PENGELOLAAN LIMBAH MEDIS PADAT - Yulis, Rahma; Nurlela, Nurlela; Sribayani, Maryam; Burhan, Burhan (Jurnal Abdi Insani, 2025)
Improper management of solid medical waste in hospitals has a high risk of causing the spread of occupational diseases and accidents in nurses. One of the occupational accidents that often occurs was being pricked by a needle or scratched by a sharp object, both while working and when disposing of waste. The purpose of this activity was to observe and assess nurses' compliance in managing solid medical waste. This community service was carried out in inpatient room A in a hospitals. There were two activities in this community service. First, compiling a measurement tool for compliance with solid medical waste management. Second, socialization related to the compliance measurement tool, the results of the assessment of nurses' compliance in waste management, the importance of compliance in managing solid medical waste, waste sorting and management procedures. The results of this activity were the availability of two observation sheets, namely: an observation sheet for compliance with the disposal of infectious, non-infectious and cytotoxic waste and an observation sheet for compliance with sharp waste management. The results of the trial of the compliance measurement tool showed that nurses' compliance in managing solid medical waste was still not optimal. The conclusion of this activity shows that compliance with solid medical waste management procedures or nurses' self-awareness towards the importance of maintaining occupational safety and health was not optimal.